2017
DOI: 10.1371/journal.pone.0169922
|View full text |Cite
|
Sign up to set email alerts
|

IL-37 Confers Protection against Mycobacterial Infection Involving Suppressing Inflammation and Modulating T Cell Activation

Abstract: Interleukin-37 (IL-37), a novel member of the IL-1 family, plays fundamental immunosuppressive roles by broadly reducing both innate inflammation and acquired immunity, but whether it is involved in the pathogenesis of tuberculosis (TB) has not been clearly elucidated. In this study, single nucleotide polymorphism (SNP) analysis demonstrated an association of the genetic variant rs3811047 of IL-37 with TB susceptibility. In line with previous report, a significant elevated IL-37 abundance in the sera and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that common genetic variation in IL37 has clinically relevant effects in inflammatory diseases. For example, rs3811047 is associated with the development of coronary artery disease and susceptibility to Mycobacterium tuberculosis infection 38 39. Additionally, rs2723187 has been associated with rapid degradation and significantly lower levels of IL-37 protein, with consequently reduced anti-inflammatory properties 40.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that common genetic variation in IL37 has clinically relevant effects in inflammatory diseases. For example, rs3811047 is associated with the development of coronary artery disease and susceptibility to Mycobacterium tuberculosis infection 38 39. Additionally, rs2723187 has been associated with rapid degradation and significantly lower levels of IL-37 protein, with consequently reduced anti-inflammatory properties 40.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have investigated the potential role of natural variants of the IL‐37 gene in human disease, including M. tuberculosis infection (Liu et al, ), coronary artery disease (Yin et al, ), and rheumatoid arthritis (Pei et al, ). In general, variants linked to increased production of IL‐37 and/or greater IL‐37 signaling are associated with lower disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, IL-37 uses IL-18Rα as a receptor to suppress immune responses. IL-37 levels were increased in the blood of M. tuberculosis patients, suggesting immunity is suppressed by a reduction in IFN-α production and the induction of M2 macrophage differentiation [155,156].…”
Section: Physiological Roles Of Il-18mentioning
confidence: 99%